R&D Spillovers through RJV Cooperation - Albert Banal-Esta\~nol; Tomaso Duso; Jo Seldeslachts; Florian Szücs (Research Policy, 2022)
We investigate how R&D spillovers propagate across firms linked through Research Joint Ventures (RJVs). Building on the framework developed by Bloom et al. (2013) which considers the opposing effects of knowledge spillovers and product market rivalry, we extend the model to account for RJV cooperation. Since the firm's decision to join a RJV is endogenous, we build a model of RJV participation. The outcome equations and RJV participation are then jointly estimated in an endogenous treatment regression model. Our main findings are that the adverse effects of product market rivalry are mitigated if firms cooperate in RJVs; and that RJV participation allows firms to better absorb technological spillovers and, thus, create value.
Keywords: L24; L44; K21; O32; 330; Spillovers; Research joint ventures; R&D; Market value